Overlap of Gastroesophageal Reflux Disease and Functional Dyspepsia and Yield of Esophagogastroduodenoscopy in Patients Clinically Fulfilling the Rome IV Criteria for Functional Dyspepsia - Quach, Duc Trong; Ha, Quoc Van; Nguyen, Chuyen Thi-Ngoc; Le, Quang Dinh; Nguyen, Doan Thi-Nha; Vu, Nhu Thi-Hanh; Dang, Ngoc Le-Bich; Le, Nhan Quang (Frontiers in Medicine, 2022)
Aims: To assess the overlap rate of gastroesophageal reflux disease (GERD) and functional dyspepsia (FD), and the yield of esophagogastroduodenoscopy (EGD) in patients clinically presenting with FD. Methods: Outpatients aged ≥18 years with typical reflux symptoms ≥ 2 times a week or clinically fulfilling the Rome IV criteria for FD (i.e., presumed FD) were recruited and underwent EGD. The endoscopic findings which could explain for patients’ symptoms were referred as clinically significant endoscopic findings (CSEFs). Patients were categorized into 3 groups after EGD: GERD only, FD only and GERD-FD overlap. Results: There were 439 patients with the mean age of 42.3 ± 11.6. Nighty-one (20.7%) patients had CSEFs: 73 (16.6%) RE, 6 (1.4%) Barrett’s esophagus and 14 (3.2%) gastro-duodenal ulcers. After excluding gastro-duodenal ulcers, the number of patients with GERD-FD overlap, GERD only and FD only were 218 (52.3%), 69 (16.2%) and 138 (34.5%), respectively. PDS was more prevalent in GERD-FD overlap compared to FD only group (72.9% vs. 44.2%, p <0.001), and in patients with the overlap of non-erosive reflux disease and FD compared to those with the overlap of reflux esophagitis/Barrett’s esophagus and FD (76.9% vs. 62.0%, p=0.035). The rate of gastro-duodenal ulcers in patients with presumed FD only was lower than those with presumed FD overlapped with GERD (0.6% vs. 4.7%, p = 0.027). Conclusions: GERD-FD overlap was more common than each of these two disorders alone, of which PDS overlap was significantly prominent. Organic dyspepsia was rare in patients clinically fulfilling the Rome IV criteria for FD.